MENGARAHKAN EKSISTENSI STANDARD OPERATING PROCEDURES PADA PROSES PENINGKATAN KUALITAS PELAYANAN PUBLIK DI DAERAH - Agus Wahyuadianto, Haris Faozan dan (Pusjar SKPP Lembaga Administrasi Negara, 2009)
Even though many policies which are concerned to public service have been issued but the factual condition has not improved much. Local governments still cannot deliver good-quality public service. Ironically, civil servants cannot even be optimized service to their own kinds, their civil servant colleagues. Seeing the public service by the customers, we can group them into two which are internal and externals customer. Both hold the same level of importance and priority. As an effort to solve that problem, it needs guidance for civil servants to do their daily tasks. We proposed Standard Operating Procedures (SOP) as an answer. Through its application, every activity is described into every step, which also contains persons in charge for those acts. More of those, SOP also describes input, time consumed and output for every activity level which are grouped inside standardized-quality section. Then we conclude that Standard Operating Procedures are a shining-path to make effective, efficient and economics bureaucracy, come into reality. Key words: public service, standard operating procedures, local government